2015
DOI: 10.1021/jp508406z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Carrier Transfer and Hot Carrier Dynamics in PbS–Au Hybrid Nanostructures

Abstract: Semiconductor−metal hybrid nanostructures (HNs) are promising materials for photovoltaics and photocatalysis because of their efficient charge separation in the excited state. However, analysis of their carrier dynamics has been limited to only a handful of HNs, such as CdSe−Au and CdS−Au. Herein, we synthesized and characterized PbS−Au HNs and examined their carrier dynamics by femtosecond near-IR pump−probe spectroscopy. A decrease in band-edge (1S) bleach yields was clearly observed in PbS−Au HNs as compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 61 publications
6
22
0
Order By: Relevance
“…Thus, the interplay between the semiconductor to metal charge transfer and the actual water reduction resulted in a nonmonotonic metal domain size effect in which optimal performance was obtained by an intermediate metal domain size. Similar phenomena have been reported recently by other groups. , …”
supporting
confidence: 92%
“…Thus, the interplay between the semiconductor to metal charge transfer and the actual water reduction resulted in a nonmonotonic metal domain size effect in which optimal performance was obtained by an intermediate metal domain size. Similar phenomena have been reported recently by other groups. , …”
supporting
confidence: 92%
“…31 The physical attributes for both the bleaches straightforwardly relate to the first excitonic absorption prominently observed in the linear optical absorption spectra. Similar to the case of CsPbBr 3 , the effective mass of both holes and electrons is quite similar in case of PbS (m e * = m h * = 0.085), 32 so the contribution of both holes and electrons to the 1S bleach of PbS is quite equal. Even in the composite system, the PbS bleach still divulges itself as a strong negative feature (Figure 4D).…”
Section: Resultsmentioning
confidence: 61%
“…In the semiconductor−metal HNs, ultrafast electron transfer from semiconductor nanocrystals to metal nanoparticles whose lifetime was much shorter than the instrumental response function was reported. 27,28 In our previous study on PbS QD−Au HNs, ultrafast electron transfer and picosecond-scale hole transfer from the bandedge states of PbS QDs to Au NPs were examined by the stateselective excitation experiments. 27 Mongin et al reported the sub-20 fs electron transfer from CdS NRs to Au NPs.…”
Section: ■ Introductionmentioning
confidence: 99%